LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR OF 31 SMALL-SIZED FISHES OF THE PARANAPANEMA RIVER BASIN - João Daniel FERRAZ; Diego Azevedo Zoccal GARCIA; Armando César Rodrigues CASIMIRO; Iago Vinicios GELLER; Fernanda Simões ALMEIDA; Mário Luís ORSI (Boletim do Instituto de Pesca)
Studies on length-weight relationships are of great importance in fishery assessments. These studies are substantial to evaluate fish population dynamics, and in communion with the relative condition factor, could provide an estimation of potential acting environmental conditions. In this paper, we evaluated the length weight relationship and relative condition factor of small sized fish species. Fish were sampled quarterly between the years 2012-2013 and 2018-2020 in lagoons and tributaries of Rosana and Taquaruçu reservoirs, located at the lower Paranapanema River basin, Brazil. The standard length (SL) in millimeters and weight (W) in grams were measured, and the length-weight relationship was calculated using linear regression analysis (W = log (a) + b log (SL)). After, the relative condition factor (Kn) was calculated from the expression We = a.SLb. Thus, the length-weight relationships of 31 species were calculated in each environment considered, giving rise to 74 population allometric coefficients (b) and relative condition factors (Kn). As result, 24 b coefficients were concentrated between 2.5 and 3.5 and seven were out of the confidence interval, while the 74 Kn values demonstrated close to the central mean and not statistical different. Our results are relevant to the conservation of fish fauna, improving knowledge regarding small-sized fish and those living environment.